2015
DOI: 10.1186/s13000-015-0269-1
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis in essential thrombocytemia and early/prefibrotic primary myelofibrosis: the role of the WHO histological diagnosis

Abstract: BackgroundVascular events represent the most frequent complications of thrombocytemias. We aimed to evaluate their risk in the WHO histologic categories of Essential Thrombocytemia (ET) and early Primary Myelofibrosis (PMF).MethodsFrom our clinical database of 283 thrombocytemic patients, we selected those with available bone marrow histology performed before any treatment, at or within 1 year from diagnosis, and reclassified the 131 cases as true ET or early PMF, with or without fibrosis, according to the WHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
(29 reference statements)
1
11
0
2
Order By: Relevance
“…In this context, one should be aware that these data are certainly representing the lower ranges as derived from centers of excellence. The extremely high incidence of 51% pre-PMF cases reported by Rupoli et al 21 was based on the failure to regard only BM specimens with fiber grade 0 (normal) and missing fiber grade 1 (minor) 22,23 as requested by the WHO classification. 1,18 In clinical practice, a rate of pre-PMF mimicking ET ranging between 20 and 30% may be closer to reality.…”
Section: Incidencementioning
confidence: 99%
“…In this context, one should be aware that these data are certainly representing the lower ranges as derived from centers of excellence. The extremely high incidence of 51% pre-PMF cases reported by Rupoli et al 21 was based on the failure to regard only BM specimens with fiber grade 0 (normal) and missing fiber grade 1 (minor) 22,23 as requested by the WHO classification. 1,18 In clinical practice, a rate of pre-PMF mimicking ET ranging between 20 and 30% may be closer to reality.…”
Section: Incidencementioning
confidence: 99%
“…Similarly, patients with prefibrotic PMF had higher 15-year risk of thrombotic events (48 %) compared to WHO-defined ET (17%) or fibrotic PMF patients (16%). By multivariate analysis, age >60 years and prefibrotic PMF were significant risk factors for developing thrombotic complications at 20 years [8]. Barosi et al demonstrated a significantly higher incidence of splanchnic vein thrombosis in prefibrotic PMF as compared to fibrotic PMF [39].…”
Section: Thrombosis In Prefibrotic Pmfmentioning
confidence: 99%
“…It is being increasingly recognized that patients with prefibrotic PMF may have a distinct thrombohemorrhagic risk profile, that might be different from that of either ET or overt PMF patients [11,8]. …”
Section: Introductionmentioning
confidence: 99%
“…4 Only a few studies have specifically addressed the issue of thrombosis in patients with PMF. [5][6][7][8] In addition, most often these studies focused on the identification of risk factors for thromboembolism, and the characteristics and distribution of thromboembolic events, and in most cases have not made a distinction between venous thrombosis and arterial thrombosis. To date, no single study performed a direct comparison of thrombosis risk in PMF with concurrent control group without myelofibrosis.…”
Section: Introductionmentioning
confidence: 99%